JUSTIFICATION OF A SYSTEMIC APPROACH IN THE SUDDEN CARDIAC DEATH PREVENTION: A POSSIBLE SOLUTION TO THE PROBLEM OF EXCESSIVE MORTALITY IN RUSSIA (LITERATURE REVIEW). PART II. SOME LIMITATIONS OF THE EXISTING SYSTEMS OF CARDIOVASCULAR MORTALITY PREVENTION AND THEIR POTENTIAL SOLUTIONS - A. S. Dimov; N. I. Maksimov (Кардиоваскулярная терапия и профилактика, 2013)
The use of pharmacotherapy in prevention is aimed at the correction of already existing consequences (pathology), rather than the prevention of causes. The number of multiple known risk factors (RFs) is steadily increasing, which limits their effective control in the real-world practice. On the other hand, focusing only on a limited number of RFs (7–9) leaves plenty of room for error. Causality is a unity of multiple RFs, unique in each individual case. Determining causality with the use of mathematical modelling can facilitate a more reliable prognostic assessment in cardiovascular disease.